Exploring the impact of algorithmic policing on social justice: Developing a framework for rhizomatic harm in the pre-crime society - Van Brakel, Rosamunde (Theoretical criminology, 2025)
This article aims to contribute to digital criminology by proposing a framework of rhizomatic harms of algorithmic policing. We propose to expand zemiologist insights with a technological and relational component, and to broaden the concept of ‘social harms’ to ‘rhizomatic harms’. Rhizomatic harms are to be understood in all their complexity, as they emerge from multiple entry points with the creation of complex layers of harms as a result. By focusing on the genealogy of rhizomatic harms of algorithmic policing in our analysis, we aim to make visible the collective, relational, cumulative and intersectional dimensions of harms and the role that macro, meso and micro processes play in harm production. The Top400 list and the use of the ProKid + algorithm in Amsterdam, The Netherlands will be used to exemplify our framework.